Patologi Psikososial dalam Keluarga Poligami: Analisis Tafsir, Hermeneutika dan Psikologi Terhadap QS. An-Nisa Ayat 3 - Syahdah Uzlifatin Niswa; M. Basuni Baihaqi; Muhamad A'thoillah Mubarok (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2025)
The discourse on polygamy in Muslim societies often stems from textual readings that overlook the socio-historical context of Qur’anic revelation. This article re-examines Q.S. an-Nis?’ [4]:3 through an interdisciplinary approach integrating tafsir studies, Paul Ricoeur’s hermeneutics, and Kurt Lewin’s field theory to analyze the psychosocial pathology within polygamous families. This qualitative library research draws upon primary sources such as Tafsir al-Mishbah, Ricoeur’s From Text to Action, and Lewin’s Field Theory in Social Science, supported by contemporary studies related to polygamy and family psychology. The findings indicate that Quraish Shihab interprets polygamy as a conditional allowance aimed at safeguarding justice and social welfare, rather than an encouraged marital model. Ricoeur’s hermeneutics demonstrates that the verse must undergo distanciation and recontextualization, shifting its meaning from legitimizing polygamy to emphasizing ethical responsibility toward vulnerable groups. Meanwhile, Lewin’s perspective shows that polygamous families tend to form a tension-filled relational field marked by emotional competition, instability, and fragmented interaction patterns. The study concludes that polygamy contains inherent theological, ethical, and psychosocial vulnerabilities, thus positioning it as an exceptional rather than normative marital structure. This interdisciplinary integration offers a holistic reading of the verse and contributes to contemporary Qur’anic studies by linking textual interpretation with psychosocial implications in modern family systems.